2000
DOI: 10.1289/ehp.00108863
|View full text |Cite
|
Sign up to set email alerts
|

Survey of bottled drinking water available in Manitoba, Canada.

Abstract: Forty domestic and imported brands of bottled water were purchased in Manitoba, Canada and examined for total dissolved solids (TDS), chloride, sulfate, nitrate-nitrogen, cadmium, lead, copper, and radioactivity. The samples showed great variation in quality, and some exceeded the Canadian Water Quality Guidelines for drinking water for TDS, chloride, and lead. Carbonation, ozonation, and type of packaging were not associated with differences in metal levels, although carbonated samples tended to show higher T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 15 publications
1
12
1
3
Order By: Relevance
“…The mean concentration of cadmium in Pip’s study (0.2±0.04 µg/l), is much lower than that of our study ( 33 ). The cadmium concentration in Yazd’s Water Distribution Network in the study of Salmani et al, (3.35±0.79 µg/l), is more than that of ours ( 34 ).…”
Section: Discussioncontrasting
confidence: 83%
“…The mean concentration of cadmium in Pip’s study (0.2±0.04 µg/l), is much lower than that of our study ( 33 ). The cadmium concentration in Yazd’s Water Distribution Network in the study of Salmani et al, (3.35±0.79 µg/l), is more than that of ours ( 34 ).…”
Section: Discussioncontrasting
confidence: 83%
“…Results for TDS were within the range 171.33-403.82 ppm with the highest concentration during the fourth sampling period in all studied stations (see Table 5). The high levels of TDS can be associated with the presence of carbonates in water samples (Pip, 2000).…”
Section: Summary Of Physicochemical Parametersmentioning
confidence: 99%
“…Three samples of distilled water showed unexpectedly high content of copper and nickel ions (88-147 and 16-35 µg/dm 3 , respectively), which was probably due to contamination in the process of distillation. Furthermore, in [116] examination of 40 Canadian and other imported water samples by methods of analytical chemistry revealed that some of the water samples failed to conform to the local standards in total content of dissolved solid substances and concentrations of chlorides and lead.…”
Section: Peculiarities Of Chemical Composition Of Bottled Watermentioning
confidence: 99%